CO2 sequestration through mineral carbonation: effect of different parameters on carbonation of Fe-rich mine waste materials - Molahid, Verma Loretta M.; Mohd Kusin, Faradiella; Syed Hasan, Sharifah Nur Munirah; Ramli, Noor Allesya Alis; Abdullah, Ahmad Makmom (MDPI, 2022)
Mineral carbonation is an increasingly popular method for carbon capture and storage that resembles the natural weathering process of alkaline-earth oxides for carbon dioxide removal into stable carbonates. This study aims to evaluate the potential of reusing Fe-rich mine waste for carbon sequestration by assessing the influence of pH condition, particle size fraction and reaction temperature on the carbonation reaction. A carbonation experiment was performed in a stainless steel reactor at ambient pressure and at a low temperature. The results indicated that the alkaline pH of waste samples was suitable for undergoing the carbonation process. Mineralogical analysis confirmed the presence of essential minerals for carbonation, i.e., magnetite, wollastonite, anorthite and diopside. The chemical composition exhibited the presence of iron and calcium oxides (39.58–62.95%) in wastes, indicating high possibilities for carbon sequestration. Analysis of the carbon uptake capacity revealed that at alkaline pH (8–12), 81.7–87.6 g CO2/kg of waste were sequestered. Furthermore, a particle size of <38 µm resulted in 83.8 g CO2/kg being sequestered from Fe-rich waste, suggesting that smaller particle sizes highly favor the carbonation process. Moreover, 56.1 g CO2/kg of uptake capacity was achieved under a low reaction temperature of 80 °C. These findings have demonstrated that Fe-rich mine waste has a high potential to be utilized as feedstock for mineral carbonation. Therefore, Fe-rich mine waste can be regarded as a valuable resource for carbon sinking while producing a value-added carbonate product. This is in line with the sustainable development goals regarding combating global climate change through a sustainable low-carbon industry and economy that can accelerate the reduction of carbon dioxide emissions.